On polynomial equations in Banach space, perturbation techniques and applications - Ioannis K. Argyros (International Journal of Mathematics and Mathematical Sciences, 1987)
We use perturbation techniques to solve the polynomial equation in Banach space. Our techniques provide more accurate information on the location of solutions and yield existence and uniqueness in cases not covered before. An example is given to justify our method.